2022
DOI: 10.1136/bmjopen-2021-059100
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of patients with multimorbidity with primary care and the association with patient activation: a cross-sectional study in Germany

Abstract: ObjectivesThis study aimed to explore the association between patient activation and patients’ experience of care among an elderly multimorbid population in Germany.DesignCross-sectional study.SettingPrimary care practices in two German settings.Participants346 patients with 3 or more chronic conditions aged 65 years and over from 36 primary care practices.Outcome measuresPatient activation was measured with the patient activation measure (PAM). To assess patient experiences with primary care, a set of questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Our earlier studies showed that e‐learning for GPs focused on activating communication with mature patients might be feasible and effective, even though observed changes in activation were subtle, and broader in patients' ratings (Rzadkiewicz et al, 2017) than in doctors' self‐ratings (Wlodarczyk et al, 2019). Activating communication skills are seen here as the GP's ability to interact with patients in a way that promotes their involvement and an active approach to treatment and health However, the present study focuses more on patient direct post‐visit experience rather than on activation itself, yet assuming the former could strongly shape the latter (Breckner et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier studies showed that e‐learning for GPs focused on activating communication with mature patients might be feasible and effective, even though observed changes in activation were subtle, and broader in patients' ratings (Rzadkiewicz et al, 2017) than in doctors' self‐ratings (Wlodarczyk et al, 2019). Activating communication skills are seen here as the GP's ability to interact with patients in a way that promotes their involvement and an active approach to treatment and health However, the present study focuses more on patient direct post‐visit experience rather than on activation itself, yet assuming the former could strongly shape the latter (Breckner et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic diseases and multiple chronic diseases or multimorbidity are the most prevalent public health challenges worldwide [1,2]. Non-communicable diseases (NCD) such as diabetes, cardiovascular and chronic respiratory diseases cause high mortality globally (74%) [2] and high expenditure on healthcare [3,4]. In Estonia in 2021, 92% of deaths resulted from NCDs, which is similar to the other Baltic countries, with the statistics for Latvia and Lithuania being 92% and 91%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, high-risk patients are defined as patients with multiple chronic conditions or a certain number of co-morbidities caused by health behavior, or who take different medications at the same time and are overusing the health care system. Proactive management of high-risk patients includes key elements such as self-efficacy and active participation in their own care process and decisionmaking [4,6]. Patient activation or proactive management could be defined as the patient's own knowledge, skills, self-confidence, and behavior to manage and improve their own health [7].…”
Section: Introductionmentioning
confidence: 99%